Gene expression and DNA methylation altering lead to the high oil content in wild allotetraploid peanut (A. monticola) - Liu, Nian; Wu, Bei; Pandey, Manish K.; Huang, Li; Luo, Huaiyong; Chen, Yuning; Zhou, Xiaojing; Chen, Weigang; Huai, Dongxin; Yu, Bolun; Chen, Hao; Guo, Jianbin; et al. (Frontiers in Plant Science, 2022)
The wild allotetraploid peanut Arachis monticola contains higher oil content than cultivated allotetraploid Arachis hypogaea. Besides the fact that increasing oil content is the most important peanut breeding objective, the proper understanding of its molecular mechanism controlling oil accumulation is still lacking. We investigated on this aspect by performing comparative transcriptomics from developing seeds between three wild and five cultivated peanut varieties. The analyses not only showed species-specific grouping transcriptional profiles but also detected two gene clusters with divergent expression patterns between two species enriched in lipid metabolism. Further analysis revealed that expression alteration of lipid metabolic genes with co-expressed transcription factors in wild peanut would lead to enhanced activity of oil biogenesis and retarded the rate of lipid degradation. In addition, bisulfite sequencing was conducted to characterize the variation of DNA methylation between wild allotetraploid (245, WH 10025) and cultivated allotetraploid (Z16, Zhh 7720) genotypes. CG and CHG contexts methylation were found to be antagonistically correlated with gene expression during seed development. Differentially methylated region analysis and transgenic assay further illustrated that variation of DNA methylation between wild and cultivated peanuts could affect oil content via altering expression of peroxisomal acyl transporter protein (Araip.H6S1B). From the results, we deduced that DNA methylation may negatively regulate lipid metabolic genes and transcription factors to subtly affect oil accumulation divergence between wild and cultivated peanuts. Our work provided the first glimpse into the regulatory mechanism of gene expression altering for oil accumulation in wild peanut and gene resources for future breeding applications.